ANALISIS KEAKURATAN HASIL TERJEMAHAN CHATGPT MENGGUNAKAN TEKNIK BACK TRANSLATION - Arju, Salsabila; Husein, Muhammad Fadhil; Sa’adah, Badriyyah; Rejeki, Annisa Mah (Universitas Islam Negeri Mataram, 2025)
In the world of translation, language translators often experience several challenges in the translation process. These can be found in differences in sound, writing, grammar, and local culture and values of a language. As time progresses and with the emergence of new technology based on artificial intelligence, translators or individuals involved in foreign languages are increasingly assisted in their translation tasks. This study aims to analyze the extent of accuracy in using ChatGPT for translating Arabic texts into Indonesian. It is a qualitative-descriptive research. The data collection method involves using literacy study methodology. The research findings indicate that ChatGPT can accurately translate Arabic into Indonesian without any grammatical errors or semantic inaccuracies. There are only a few differences observed in word choice, which are deemed to be shorter, concise, and more efficient in translation than Google Translate.